RAQAMLASHTIRISH JARAYONIDA “TA’LIMDA AXBOROT TEXNOLOGIYALARI” FANINI ZAMONAVIY ELEKTRON AXBOROTTA’LIM RESURS ASOSIDA O’QITISH VOSITASI SIFATIDA QO’LLASH (Conference Zone, 2022)
This article will focus on the concepts and principles of digitization of education at the present stage of development of the information society, the use of digital technologies in education, their integration into the educational process, and professional competencies. Therefore, this article discusses the stages of creating electronic information and educational resources and the organization of training based on them